Developing and Analysing a Photovoltaic (PV) Renewable Energy Source with Particle Swarm Optimization (PSO) Algorithm for Battery Management in Grid Environment Power Quality - Arulmurugan, V. S.; Rajeswari, C.; Bharathidasan, P.; Balaji, K. (SN computer science, 2024)
Renewable energy is the most viable option for rural electrification due to its widespread availability. In the previous work balance between power generation and load power, with batteries serving as a backup source for both Photovoltaic (PV) and wind energy are having drawbacks such as maintains a constancy between source and load request, even in the face of sudden changes in load and fluctuations in PV and wind power generation. To solve the problem micro grid comprising of a Photovoltaic (PV) array battery energy storage are developed in this work. One of the primary sources of renewable energy is photovoltaic energy, which can vary significantly depending on temperature, cell type, and irradiance levels. In wind power generation, the rotor's accessibility allows for the Doubly Fed Induction Generator (DFIG) to regulate the stator power, with the overall power being derived from the rotor. Maximum Power Point Tracking (MPPT) is based on Particle Swarm Optimization (PSO) and procedures the PV module's current output in relation to the battery voltage. It calculates the power maximum output of the element and changes optimum voltage for charging the battery with the maximum amount of power. In a hybrid system, there are two buses and AC bus and a DC bus, a single AC bus, with an AC/AC converter connecting the wind turbine and a DC/AC converter connecting the PV to the AC bus. The DC bus is used to connect sources with a DC current, while the AC bus is used for sources with an alternating current. This micro grid is simulated using MATLAB/Simulink tool and gain better power quality output.